Resistance to moment-normal force interaction of I-shaped steel sections - Rombouts, I.M.J.; Snijder, H.H.; Dekker, R.W.A.; Teeuwen, P.A. (Journal of constructional steel research, 2016)
This paper describes the assessment of the EN 1993-1-1 design rules for cross-section resistance to moment-normal force interaction (M-N interaction). Besides the fact that the Eurocode design rules show unconservative predictions of the reduced plastic moment capacity for the presence of relatively low normal force, the recommended partial factor is γM0=1.00 and relative large shear forces up to 50% of the shear resistance are allowed. This means that, neglecting a possible benefit from strain hardening, the EN 1993-1-1 design rules have no spare capacity available in the section. A few large scale experiments for M-N interaction were performed on HEA240 (S355JR) sections. In order to simulate the behaviour of a section to M-N interaction, a Finite Element Model was created in Abaqus/CAE. The model was validated against the experimental test results. Then, 1188 numerical test results were generated. A statistical evaluation to assess the design rule against these numerical test results showed that the recommended value γM=1.00 of the partial factor used in the EN1993-1-1 design rules is statistically acceptable for I-shaped sections in steel grades S235 and S355. For S460 it is necessary to use γM=1.10 based on the currently available statistical material data. •The material behaviour of an HEA section varies over the cross-section.•Eurocode design rules show unconservative approximations.•Experimental My-N interaction behaviour is similar to theoretical behaviour.•Benefit from strain hardening only applies to cross-sections with stocky flanges.•Current partial safety factor is acceptable for S235/S355, but too small for S460.